Code and Data Readme for “Modeled subglacial water flow routing supports localized intrusive heating as a possible cause of basal melting of Mars’ south polar ice cap" - Arnold, Neil; Conway, Susan; Butcher, Frances; Balme, Matthew (2019)
Computer code and derived data developed during the research reported in "Modeled subglacial water flow routing supports localized intrusive heating as a possible cause of basal melting of Mars’ south polar ice cap" published in Journal of Geophysical Research-Planets. See the file 'Code and Data Readme.rtf' for detailed information about the contents of this dataset.